2013
DOI: 10.1136/bmj.f3306
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia and pneumonia related mortality in patients with COPD treated with fixed combinations of inhaled corticosteroid and long acting  2 agonist: observational matched cohort study (PATHOS)

Abstract: Objective To investigate the occurrence of pneumonia and pneumonia related events in patients with chronic obstructive pulmonary disease (COPD) treated with two different fixed combinations of inhaled corticosteroid/long acting β 2 agonist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
164
0
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(182 citation statements)
references
References 36 publications
(43 reference statements)
12
164
0
6
Order By: Relevance
“…Also the previously mentioned PATHOS study supported this observation [23]. Compared with budesonide/formoterol combination, rate of pneumonia and admission to hospital were higher in patients treated with fluticasone/salmeterol combination, with a rate ratio 1.73 (CI: 1.57e1.90; P < 0.001) and 1.74 (1.56e1.94; P < 0.001), respectively.…”
Section: Potential Side Effects Of Ics In Copd: the Risk Of Pneumoniasupporting
confidence: 68%
See 1 more Smart Citation
“…Also the previously mentioned PATHOS study supported this observation [23]. Compared with budesonide/formoterol combination, rate of pneumonia and admission to hospital were higher in patients treated with fluticasone/salmeterol combination, with a rate ratio 1.73 (CI: 1.57e1.90; P < 0.001) and 1.74 (1.56e1.94; P < 0.001), respectively.…”
Section: Potential Side Effects Of Ics In Copd: the Risk Of Pneumoniasupporting
confidence: 68%
“…The exacerbation rates in the budesonide/formoterol and fluticasone/salmeterol groups were 0.80 and 1.09 per patient-years, respectively (p < 0.0001), and yearly rates for COPD-related hospitalizations were 0.1 and 0.21, respectively (p < 0.0001). All other healthcare outcome were also significantly reduced with budesonide/formoterol vs fluticasone/salmeterol combination [22,23]. Therefore, also this study suggests that long-term with budesonide/ formoterol combination was associated with fewer healthcare utilization-defined exacerbations than fluticasone/salmeterol combination in patients with moderate and severe COPD.…”
Section: Comparative Clinical Efficacy Of Fluticasone/salmeterol and supporting
confidence: 51%
“…Two observational studies also found a lower risk of severe pneumonia with budesonide compared with fluticasone [65,66]. There is the possibility, however, that in both jurisdictions in which these studies were carried out, use of the formoterol/budesonide combination may have been a marker of asthma where ICS are not associated with an excess in pneumonia [67].…”
Section: Safety Of Ics and Laba/ics In Copdmentioning
confidence: 99%
“…TORCH was the largest RCT; it included more than 6,000 patients and was the first trial to show significantly increased risk of pneumonia (hazard ratio [HR], 1.64; 95% confidence interval [CI], 1.33-2.02) (19). Several other trials demonstrated increased risk of pneumonia among ICS users (3-7, 17, 20, 21) (23)(24)(25). This could be related to the difference between fluticasone and budesonide in potency or clearance rates from airways (26,27).…”
Section: Pneumoniamentioning
confidence: 99%